1968
DOI: 10.1192/bjp.114.517.1537
|View full text |Cite
|
Sign up to set email alerts
|

Reading Retardation, Dyslexia and Delinquency

Abstract: In 1932 Monroe wrote that “inability to read may be one of the prolonged school problems to which parents and agencies become adapted until the child drifts into truancy and incorrigibility”. This observation, if true, is highly pertinent to the problems of present day society, and, for this reason, a personal study was made of delinquent boys between the ages of 12 and 17 years referred by the courts for assessment at a London Remand Home and Classifying Centre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
19
0

Year Published

1973
1973
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 9 publications
2
19
0
Order By: Relevance
“…In fact, Maughan, Gray, and Rutter (1985) found that approximately 67% of the individuals with LD whom they studied had records of juvenile delinquency. Their data are consistent with Critchley's (1968), who found an incidence rate of 60%. Unfortunately, few studies that address this problem spell out the nature of the LD, although reading problems are frequently noted.…”
supporting
confidence: 91%
“…In fact, Maughan, Gray, and Rutter (1985) found that approximately 67% of the individuals with LD whom they studied had records of juvenile delinquency. Their data are consistent with Critchley's (1968), who found an incidence rate of 60%. Unfortunately, few studies that address this problem spell out the nature of the LD, although reading problems are frequently noted.…”
supporting
confidence: 91%
“…Recent research has increasingly emphasized the importance of exploring early educational failure as a possible precursor of delinquency (Berman, 1974;Kratoville, 1974;Kvaraceus, 1971;Rutter, 1975Rutter, , 1979. In a few instances, retrospective, long-term studies have attempted to trace the academic and school histories of delinquent populations, but findings have not been consistent (Critchley, 1968;Rutter, 1975Rutter, , 1979Zinkus, Gottlieb and Gottlieb, 1978). Similarly, follow-up studies of children with learning disabilities and/or brain damage have not provided any clear-cut explanation for the development of conduct disorders (Rutter, 1984, Schonhaut andSatz, 1981, inpress;Spreen, 1984).…”
Section: Introductionmentioning
confidence: 93%
“…Delays in reading skill ranging from two to five years have been documented in delinquent youth (Critchley, 1968). Other investigators have established less dramatic lags (Silberberg and Silberberg, 1971;Tarnopol, 1970;Wolfgang, Figlio & Sellin, 1972).…”
Section: Introductionmentioning
confidence: 94%
“…Burt, 1925;Healey, 1933;Ferguson, 1952;Critchley, 1968). Both are common problems and for this reason alone the two conditions will often co-exist.…”
Section: Introductionmentioning
confidence: 95%